Bimolecular crystals of fullerenes in conjugated polymers and the implications of molecular mixing for solar cells - Mayer, A.C.; Toney, M.F.; Scully, S.R.; Rivnay, J.; Brabec, Christoph; Scharber, Markus C.; Koppe, Markus; Heeney, Martin; Mcculloch, Iain; Mcgehee, Michael D. (Advanced Functional Materials, 2009)
The performance of polymerfullerene bulk heterojunction solar cells is heavily influenced by the interpenetrating nanostructure formed by the two semiconductors because the size of the phases, the nature of the interface, and molecular packing affect exciton dissociation, recombination, and charge transport. Here, X-ray diffraction is used to demonstrate the formation of stable, well-ordered bimolecular crystals offullerene intercalated between the side-chains of the semiconducting polymer poly(2,5-bis(3-tetradecylthiophen- 2-yl)thieno[3,2-b]thiophene. It is shown that fullerene intercalation is general and is likely to occur in blends with both amorphous and semicrystalline polymers when there is enough free volume between the side-chains to accommodate the fullerene molecule. These findings offer explanations for why luminescence is completely quenched in crystals much larger than exciton diffusion lengths, how the hole mobility of poly(2-methoxy-5-(3',7'- dimethyloxy)-p-phylene vinylene) increases by over 2 orders of magnitude when blended with fullerene derivatives, and why large-scale phase separation occurs in some polymer:fullerene blend ratios while thermodynamically stable mixing on the molecular scale occurs for others. Furthermore, it is shown that intercalation offullerenes between side chains mostly determines the optimum polymer:fullerene blending ratios. These discoveries suggest a method ofintentionally designing bimolecular crystals and tuning their properties to create novel materials for photovoltaic and other applications. © 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.